Metabolomic analysis of prostate cancer risk in a prospective cohort: The alpha‐tocolpherol, beta‐carotene cancer prevention (ATBC) study. Issue 9 (9th May 2015) - Mondul, Alison M.; Moore, Steven C.; Weinstein, Stephanie J.; Karoly, Edward D.; Sampson, Joshua N.; Albanes, Demetrius
<x xml:space="preserve">Abstract</x> Despite decades of concerted epidemiological research, relatively little is known about the etiology of prostate cancer. As genome‐wide association studies have identified numerous genetic variants, so metabolomic profiling of blood and other tissues represents an agnostic, "broad‐spectrum" approach for examining potential metabolic biomarkers of prostate cancer risk. To this end, we conducted a prospective analysis of prostate cancer within the Alpha‐Tocopherol, Beta‐Carotene Cancer Prevention Study cohort based on 200 cases (100 aggressive) and 200 controls (age‐ and blood collection date‐matched) with fasting serum collected up to 20 years prior to case diagnoses. Ultrahigh performance liquid chromatography/mass spectroscopy and gas chromatography/mass spectroscopy identified 626 compounds detected in >95% of the men and the odds ratio per 1‐standard deviation increase in log‐metabolite levels and risk were estimated using conditional logistic regression. We observed strong inverse associations between energy and lipid metabolites and aggressive cancer (p = 0.018 and p = 0.041, respectively, for chemical class over‐representation). Inositol‐1‐phosphate showed the strongest association (OR = 0.56, 95% CI = 0.39–0.81, p = 0.002) and glycerophospholipids and fatty acids were heavily represented; e.g., oleoyl‐linoleoyl‐glycerophosphoinositol (OR = 0.64, p = 0.004), 1‐stearoylglycerophosphoglycerol (OR=0.65, p = 0.025), stearate (OR=0.65, p = 0.010) and docosadienoate (OR = 0.66, p = 0.014). Both alpha‐ketoglutarate and citrate were associated with aggressive disease risk (OR = 0.69, 95% CI = 0.51–0.94, p = 0.02; OR = 0.69, 95% CI = 0.50–0.95, p = 0.02), as were elevated thyroxine and trimethylamine oxide (OR = 1.65, 95% CI = 1.08–2.54, p = 0.021; and OR = 1.36, 95% CI = 1.02–1.81, p = 0.039). Serum PSA adjustment did not alter the findings. Our data reveal several metabolomic leads that may have pathophysiological relevance to prostate carcinogenesis and should be examined through additional research.